2009
DOI: 10.1002/ana.21542
|View full text |Cite
|
Sign up to set email alerts
|

β2‐adrenoceptors are critical for antidepressant treatment of neuropathic pain

Abstract: Stimulation of beta(2)-AR is necessary for nortriptyline to exert its antiallodynic action against neuropathic pain. These findings provide new insight into the mechanism by which antidepressants alleviate neuropathic pain. Our results also raise the question of a potential incompatibility between beta-blockers that affect beta(2)-AR and antidepressant drugs in patients treated for neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 38 publications
11
90
0
1
Order By: Relevance
“…In this case, it requires 1 to 2 weeks of treatment to observe a lasting relief of the neuropathic allodynia. When the treatment is interrupted, a relapse is usually observed within 3 to 4 days 18 . Beside some antidepressants, gabapentinoids are the other first-choice treatments for neuropathic pain.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, it requires 1 to 2 weeks of treatment to observe a lasting relief of the neuropathic allodynia. When the treatment is interrupted, a relapse is usually observed within 3 to 4 days 18 . Beside some antidepressants, gabapentinoids are the other first-choice treatments for neuropathic pain.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Similar to clinical observations: gabapentinoids display both an acute short-lasting analgesic action at high dose and a delayed sustained relieving action that is observed after a few days of treatment, tricyclic antidepressants and selective serotonin and noradrenaline reuptake inhibitors have no acute analgesic effect at relevant dose but they display a delayed sustained relieving action that requires 1 to 2 weeks of treatment, and the selective serotonin reuptake inhibitor fluoxetine is ineffective 16 . The model is thus appropriate to study the molecular mechanism underlying these treatments [16][17][18]44,45,47 , which may reveal new therapeutic targets to test in patients [48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These animal models permit the pain thresholds in response to different painful stimuli to be determined (mechanical, thermal, electrical, etc.) and using such approaches, it was demonstrated that diverse antidepressants reduce allodynia in a model of peripheral neuropathy, such as desipramine, venlafaxine, reboxetin and nortriptyline (Yalcin et al, 2009a;2009b). Moreover, anti-allodynic effects of amitriptyline and nortriptyline (TCAs) have been described in models of chronic but not acute pain (Benbouzid et al, 2008a), and fluoxetine (SSRI) was seen to be ineffective at relatively high doses.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Indeed, amitriptyline analgesia is abolished in 2A -adrenoceptor KO mice in the hot plate and tail-flick tests (Ozdogan et al, 2004), suggesting that 2A -adrenoceptors play a significant role in mediating the acute analgesic effects of amitriptyline, although other neurotransmitter systems may also be involved. The expression of -adrenoceptors in the descending noradrenergic inhibitory pathway (Nicholson et al, 2005) also suggests a role for these receptors in the analgesic effects of antidepressants and the 2 subtype has been shown to fulfil a critical role in the antiallodynic effects of nortriptyline (Yalcin et al, 2009a), venlafaxine and desipramine (Yalcin et al, 2009b While the majority of studies of the serotonergic action of antidepressants have focused specifically on antidepressant effects, antidepressant-induced analgesia has been studied in mice lacking Lmx1b (Zhao et al, 2007), a LIM homeodomain-containing transcription factor required for postmitotic differentiation of serotonergic neurons (Ding et al, 2003). These mice display dysfunctional central serotonergic neurotransmission and thus, they represent a novel tool to study the mode of action of antidepressants.…”
Section: Lessons From Knockout Micementioning
confidence: 99%